Implantes curtos do tipo cone-Morse: proporção coroa-implante - Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia de; Santiago Júnior, Joel Ferreira [UNESP]; Almeida, Daniel Augusto de Faria [UNESP]; Honório, Heitor Marques; Verri, Fellippo Ramos [UNESP] (My University, 2013)
The purpose of this study was to analyze the biomechanical interactions in bone tissue between short implants and implant-supported crowns with different heights. Two models were made using the programs InVesalius 3.0, Rhinoceros 4.0 and Solidworks 2010. The models were established from a bone block with the short implant (3.75 x 8.5 mm) with geometry Morse taper connection (MT). The height of the crown (cemented) was set at 10.0 mm and 15.00 mm. The models were processed by programs and 10 NEiNastran Femap 10.0. The force applied was 200N (vertical) and 100N (oblique). The results were plotted on maps Voltage Maximum Principal. Statistical analysis was performed using ANOVA. The results showed that the increase in crown height, increased stress concentration in the crown of 15 mm under oblique loading (p <0.001), the oblique loading has significantly expanded the area of stress concentration (p <0.001). Conclusion:the increase of the crown increased the stress concentration, being statistically significant for short implants Morse taper. The mesial and distal region had the highest concentration of stresses under oblique loading. The oblique loading was more harmful when compared with axial loading, being statistically significant.

A proposta deste estudo foi analisar as interações biomecânicas no tecido ósseo entre implantes curtos e coroas implantossuportadas com diferentes alturas. Dois modelos foram confeccionados usando os programas Invesalius 3.0, Rhinoceros 4.0 e Solidworks 2010. Esses modelos foram constituídos de um bloco ósseo com implante curto (3,75 x 8,5 mm) cone Morse. A altura da coroa (cimentada) foi estabelecida em 10.00 mm e 15.00 mm. Os modelos foram processados pelos programas Femap 10 e NeiNastran 10.0. A força aplicada foi de 200N (vertical) e 100N (oblíqua). Os resultados foram plotados em mapas de Tensão Máxima Principal. A análise estatística foi realizada com ANOVA. Os resultados apontaram que o aumento da altura da coroa ampliou a concentração de tensões na coroa de 15 mm, sob carregamento oblíquo (p<0.001), e a carga oblíqua ampliou consideravelmente a área de concentração de tensões (p<0.001). O aumento da coroa ampliou a concentração de tensões sendo estatisticamente significante para implantes curtos do tipo cone Morse. A região distal e mesial apresentaram a maior concentração de tensões, sob carregamento oblíquo. O carregamento oblíquo foi o mais prejudicial, quando comparado com o carregamento axial, sendo estatisticamente significante.
Morse Taper implants short: crown-to-implant ratio
Keywords: Dental implants; Biomechanics; Finite element analysis; Analysis of variance; Implantes dentários; Biomecânica; Análise por elementos finitos; Análise de variância